ASSESSING THE SUITABILITY OF SCHOOL SURROUNDINGS FOR CHILDREN’S MOBILITY USING A PARTICIPATORY MULTI-CRITERIA APPROACH: THE CASE OF A PRIMARY SCHOOL IN GUELMA, ALGERIA - Meryem Lamari; Youcef Lazri; Hocine Bougdah (International Journal of Innovative Technologies in Social Science, 2024)
The surroundings of the school are sensitive spaces that play an integral role in the sustainability of children’s mobility on their journeys to school. Indeed, this vulnerable category is in daily interaction with an urban environment that must be friendly and suitable. This work is based on the synthetic criteria and indicators of UNICEF and Its agencies, which are appropriate for the children’s needs. The study presented here will evaluate the suitability of the school surroundings for children’s mobility through a participatory multi-criteria analysis that focuses on the child as an inseparable actor in the analysis process. The case study for this field of investigation is a primary school located in the centre of Guelma, a city in the Northeast of Algeria. A survey questionnaire was conducted to collect quantitative and qualitative data on their experience of mobility, from a sample of 169 pupils (5 to 12 years old). The synthetic criteria were weighted by frequency analysis using SPSS according to the surveyed population. The data shows that 23 % of the participants ranked the stability of the social structure criterion in the first position. The suitability of multi-criteria approach will be tested by applying it to the synthetic criteria ranked first. The results show that the majority of social indices with a direct influence on children’s mobility have negative performance values, synonymous with non-suitability. Other indicators have low values of positive performance, synonymous with an average suitability level, which still needs to be improved. Overall, this participatory multi-criteria analysis shows that the school environments studied do not satisfactorily meet the safety and well-being requirements that are essential for sustainable school mobility adapted to children’s needs.